2017
DOI: 10.4317/jced.53677
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of Nano-Hydroxyapatite preparation and Calcium Sucrose Phosphate on microhardness of deciduous teeth after iron drop exposure - An in-vitro study

Abstract: BackgroundTo evaluate and compare the microhardness of deciduous teeth treated with nano-hydroxyapatite and calcium sucrose phosphate after iron drop exposure.Material and MethodsTwenty healthy anterior deciduous teeth were collected and stored in 0.9% saline solution at room temperature. All the teeth were immersed in artificial saliva in an incubator shaker at 37° for an hour and then subjected to Vickers microhardness test at 100g load for 5 seconds. The teeth were then immersed in iron drop for 5 minutes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…In addition, apatite formed in an environment containing more calcium and phosphate is expected to contain less CO2 and less Mg by replacing them with calcium and phosphate, making enamel more acid resistant and increasing its surface hardness levels ( 12 ). This result is in agreement with Swarup JS et al ( 1 ), Rathi N et al ( 13 ), and Ebadifar A et al ( 7 ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, apatite formed in an environment containing more calcium and phosphate is expected to contain less CO2 and less Mg by replacing them with calcium and phosphate, making enamel more acid resistant and increasing its surface hardness levels ( 12 ). This result is in agreement with Swarup JS et al ( 1 ), Rathi N et al ( 13 ), and Ebadifar A et al ( 7 ).…”
Section: Discussionsupporting
confidence: 92%
“…22 Rani et al 23 and Thomas et al 24 demonstrated the superiority of CaSP in increasing the mean surface hardness as compared to CPP-ACP at 12th and 15th day of remineralization. Likewise, Rathi et al 7 also showed increase in mean microhardness of enamel after CaSP application.…”
Section: Microhardness Assessmentmentioning
confidence: 84%
“…An increase in the mean microhardness of enamel was evident in all the studies, post-application of CaSP. 6,7,12,14,[19][20][21][22][23][24] In addition, CaSP was also found to be effective in restoring the color of white spot lesion(s) and fluorotic enamel to that of normal enamel. 26 CaSP was also proven to be superior to other remineralizing agents in controlling the lesion depth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, they have enhanced wettability which helps it to form a thin but strong layer on enamel surface that bonds to the tooth structure. [ 16 17 ] Finally, grape seed extract (GSE) has recently been advocated for its positive effects on the RML process of artificial carious lesions of the enamel in human primary teeth due to the GSE being rich in proanthocyanidin (PA), which is mainly composed of monomeric catechin and epicatechin, gallic acid, and polymeric and oligomeric procyanidins. PA has been reported to strengthen collagen-based tissues by increasing collagen cross-links.…”
Section: Introductionmentioning
confidence: 99%